Development of a Marine LPG-Fueled High-Speed Engine for Electric Propulsion Systems - Kang Woo Chun; Myongho Kim; Jae-Jung Hur (Journal of Marine Science and Engineering, 2022)
As regulations on emissions from ships become stricter worldwide, new propulsion systems and the use of eco-friendly fuel are being introduced as alternative solutions. Therefore, many studies on electric propulsion systems using various power sources are being conducted. Conventional diesel propulsion systems are available from small to large scale, but in the case of LPG propulsion systems, some specifications are limited, and their application is impossible. In addition, due to the limitations of the companies participating in the development of small and medium-sized engines, marine empirical research into existing shore engines is required rather than developing new engines. In this study, a generator using LPG fuel was developed for such an eco-friendly electric propulsion system and tested in the field. Accordingly, a 230 kW-class waterjet type LPG engine for electric propulsion was developed and developed for patrol ships, which are small and medium-sized ships. A system that considers the marine environment was developed, and various data were recorded through test operation under various loads. The results of this study can be used for the development of various auxiliary engine systems, and the test operation procedure of this development can be applied to the development of small and medium-sized LPG engines of different capacities. In addition, it can have a big impact on the business of converting marine engines from onshore engines. However, the development costs and improving the efficiency are still areas to be further improved through future research.